Comparison of hemodynamic parameters in treatment-naïve and pre-treated patients with pulmonary arterial hypertension in the randomized phase III PATENT-1 study - Galiè, Nazzareno; Grünig, Ekkehard (The journal of heart and lung transplantation, 2017)
Background: Detailed hemodynamic data from the phase III PATENT-1 study of riociguat in patients with pulmonary arterial hypertension (PAH) were investigated. Methods: Patients with PAH who were treatment naïve or pre-treated with endothelin receptor antagonists or non-intravenous prostanoids were randomly assigned to riociguat up to 2.5 mg 3 times a day or placebo. Hemodynamic parameters were assessed at baseline and week 12. Results: Riociguat significantly decreased pulmonary vascular resistance in treatment-naïve (n = 221; least squares [LS] mean difference −266 dyne∙sec∙cm−5 [95% confidence interval (CI) −357 to −175; p < 0.0001]) and pre-treated (n = 222; LS mean difference −186 dyne∙sec ∙cm−5 [95% CI −252 to −120; p < 0.0001]) patients and significantly increased cardiac index (LS mean difference +0.7 [95% CI 0.5 to 0.8] and +0.5 [95% CI 0.3 to 0.7], respectively [both p < 0.0001]). Mean pulmonary artery pressure (p = 0.0056 and p = 0.0019 for treatment-naïve and pre-treated patients, respectively), mean arterial pressure (both p < 0.0001), and systemic vascular resistance (both p < 0.0001) were significantly reduced, and there was an increase in mixed venous oxygen saturation (p < 0.0001 and p = 0.0004, respectively). Results were similar in patients pre-treated with endothelin receptor antagonists and patients pre-treated with non-intravenous prostanoids. Improvements in 6-minute walking distance correlated very weakly with improvements in pulmonary vascular resistance (r = −0.21 [95% CI −0.30 to −0.11; p < 0.0001]) and cardiac index (r = 0.16 [95% CI 0.06 to 0.25; p < 0.0016]). Conclusions: Riociguat significantly improved hemodynamic parameters in pre-treated and treatment-naïve patients with PAH.